PENGARUH VARIASI FAKTOR EKSPOSI (TEGANGAN TABUNG DAN ARUS WAKTU) SERTA PITCH TERHADAP COMPUTED TOMOGRAPHY DOSE INDEX (CTDI) DI UDARA MENGGUNAKAN CT DOSE PROFILER - Puput Khusnaiatul; Eko Hidayanto; Zaenal Arifin; Choirul Anam (Youngster Physics Journal, 2014)
The measurements of CTDI have been done as the method used to measure of dose in CT scans. The Measurement method is CTDI air method. Measuremeans of CTDI air using the CT dose profiler was placed in the center of the gantry rotation using tube voltage variations (80 kVp, 100 kVp, 120 kVp and 140 kVp), current time variations (100 mAs, 200 mAs, 300 mAs and 370 mAs) and pitch variations (0,75, 1, 1,25 and 1,5). The results of measurements  tube voltage variations in 370 mAs, pitch 1 and collimation 5 mm were 28,8-105 mGy, current time variations in tube voltage120 kVp, pitch 1 and collimation 5 mm were 19,7-73 mGy and Pitch variation in tube voltage 120 kVp, effective current time 370 mAseff, and collimation 5 mm were 55,9-116 mGy. The measurement results showed that greater the tube voltage, current time and pitch are used then the resulting CTDI air gets greater. The smaller tube voltage, current time and pitch are used then the resulting CTDI air gets smaller. FWHM and  geometric effisiency value of tube voltage variation were 6,2-6,37 mm and 68,40%-71,30%, current time variation were 6,17-6,27 mm and 69,5%-72,5% and pitch variation were 6,19-6,51 mm and 69,2%-71,4%. FWHM values of the three variations were larger than the width of collimation because the penumbra effect and geometric effisiency values were still within tolerance limits of 55%-75%. Keywords: CT dose profiler, CTDI air, FWHM, geometric effisiency